ANALISIS PELAKSANAAN PROGRAM KELUARGA HARAPAN (PKH) DALAM RANGKA PENGURANGAN ANGKA KEMISKINAN DI KABUPATEN BANTUL TAHUN 2018 - Sukma Aprilia Puntorini; Purnomo, Eko Priyo (JKKP (Jurnal Kesejahteraan Keluarga dan Pendidikan), 2020)
This study aims to analyze the implementation of the Family Hope Program (PKH) in the context of reducing the poverty rate in Bantul Regency in 2018. The method used in this study is a qualitative method, the type of data used is secondary data, secondary data, namely collecting data and information obtained by through documentation or archives in Bantul Regency. The results showed that Bantul Regency knew the extent of community understanding of PKH, namely through socialization, as well as providing entrepreneurship training so that beneficiary families (KPM) could be more productive. In addition, Bantul Regency still has several obstacles in implementing PKH. With the PKH, it can make KPM more productive, because there is entrepreneurship training. This entrepreneurship training can make KPM more creative and can increase income in the family. In addition, Bantul Regency still has several obstacles in implementing PKH. The obstacles to PKH in Bantul Regency are the lack of funds to provide supporting facilities and infrastructure for PKH implementers, the lack of availability of human resources, namely PKH facilitators, decreased compliance of PKH participants, and PKH recipient data not being updated so that it is not well targeted. So it is better if this PKH program involves the village government so that someone monitors it directly, the community fulfills its obligations as PKH participants, and there is updating of PKH participant data. Abstrak Penelitian ini bermaksud untuk menganalisis pelaksanaan Program Keluarga Harapan (PKH) dalam rangka pengurangan angka kemiskinan di Kabupaten Bantul Tahun 2018. Program Kelarga Harapan adalah program bantuan tunai yang bersyarat dalam bidang pendidikan dan kesehatan. PKH ini membantu untuk mencapai tujuan Pembangunan Millenium, ada 5 komponen yaitu mengurangi penduduk miskin dan kelaparan, kesetaraan gender, pendidikan dasar, pengurangan angka kematian bayi dan balita, serta pengurangan angka kematian ibu melahirkan. Metode yang digunakan dalam penelitian ini adalah metode kualitatif jenis data yang digunakan adalah data sekunder, data sekunder yaitu mengumpulkan data dan informasi yang didapat dengan melalui dokumentasi atau arsip yang ada di Kabupataen Bantul. Hasil penelitian menunjukkan bahwa Kabupaten Bantul untuk mengetahui sejauh mana pemahaman masyarakat tentang PKH yitu dengan sosialisasi. Selain itu Kabupaten Bantul masih memiliki beberapa hambatan dalam melaksanakan PKH. Kata kunci: analisis, kemiskinan, PKH, sosialisasi